2022
DOI: 10.1016/j.spinee.2021.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular lipid concentration increased in localized regions of the lumbar muscles following 60 day bedrest

Abstract: BACKGROUND CONTEXT: Prolonged bedrest induces accumulation of intramuscular lipid concentration (ILC) in the lumbar musculature; however, spatial distribution of ILC has not been determined. Artificial gravity (AG) mitigates some adaptations induced by 60 day bedrest by creating a head-to-feet force while participants are in a supine position. PURPOSE: To quantify the spatial distribution of accumulation of ILC in the lumbar musculature after 60 day bedrest, and whether this can be mitigated by AG exposure. ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Therefore, lacking exercise and motion, the process of muscle degeneration in frail patients would be more severe than in those not [ 25 ]. Martino et al found that intramuscular lipid concentration increased in localized regions of the lumbar muscles following 60-day bed rest [ 26 ]. Previous studies have shown nutritional risk factors were independently associated with physical pre-frail/frail condition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lacking exercise and motion, the process of muscle degeneration in frail patients would be more severe than in those not [ 25 ]. Martino et al found that intramuscular lipid concentration increased in localized regions of the lumbar muscles following 60-day bed rest [ 26 ]. Previous studies have shown nutritional risk factors were independently associated with physical pre-frail/frail condition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that extreme sedentary behaviour may result in lumbar multifidus atrophy. For example, spaceflight 18 , 19 and prolonged head-down tilt bed rest 20 may reduce lumbar multifidus size and increase IMAT; changes that are potentially reversible with exercise training 21 . Our results do accord with studies reporting little to no relations between lumbar multifidus IMAT and lumbar multifidus function 22 , prognostic factors associated with exercise outcomes for patients with low back pain 23 , as well as lumbar multifidus size and tests of physical performance 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effect makes the muscle gradually thin and degenerate, eventually replaced by adipose tissue ( 59 ). Previous studies have indicated a higher accumulation of adipose tissue in PSMs is related to physical inactivity ( 54 , 60 ). Movement and gravitational loading are essential for maintaining a healthy spine.…”
Section: Mechanisms Of Ivdd Involved In Fat Infiltration Of Psmsmentioning
confidence: 92%
“…In response to decreased use, the lumbar spine undergoes adaptive remodeling ( 62 ). Adverse effects include lumbopelvic muscle atrophy, fat accumulation in PSMs, reduced lumbar lordosis, and altered disc hydration status ( 54 , 61 ). Surprisingly, Hides et al.…”
Section: Mechanisms Of Ivdd Involved In Fat Infiltration Of Psmsmentioning
confidence: 99%